Data play: Participatory visualisation to make sense of data. Issue 1 (24th October 2017) - Anderson, Theresa Dirndorfer; Knight, Simon; Tall, Kelly
ABSTRACT: This visual presentation invites conference participants to use data play to tap into the creative capacity of visual ideation for individual and collaborative learning about (their) data. The authors discuss the application of a hand‐drawn self‐visualisation approach to data understanding to draw attention to the space of representational possibilities, the power of representation interactions and the performativity of information representation. The visual presentation takes an interactive and emergent approach to exploring tactile, visual modes of self‐expression, sense‐making and communication, inviting conference participants to dabble and doodle and think visually about the conference. Over time, the visual artefact will be transformed by and through this community input. Through this collective visual practice, we heed Lupi's call to bring data to life as we make sense of our data traces.